An Investigation into Students’ Understanding about the Concepts of Energy at Senior Secondary Level - Sharma, S.V. (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Present study entitled “An Investigation into Students‟ Understanding about the Concepts of Energy at Senior Secondary Level” was conducted on senior secondary students of a Government School. Students were divided into two groups namely, experimental and controlled to investigate their understanding about the concepts of energy. Analysis of the students‟ responses clearly revealed a significant difference between students‟ understanding of experimental and controlled groups about the concepts of energy. The same was attributed due to the constructivist approach of teaching learning.